(untitled) (The International Journal of Educational Sciences and Arts, 2023)
Education at the kindergarten level is currently witnessing an increasing demand and a great diversity of its types, unprecedented, which requires educational systems to respond to this demand by providing more opportunities for these systems to change, develop, and improve the educational process in its various aspects. Hence, the organizational structure of any educational institution is the driving axis of the administrative process, and since the work cannot be carried out except after planning it, and with a solid base for its organization, this organization is concerned with distributing the work among the employees, each according to his specialization and experience; Therefore, comprehensive quality management in education means planning, directing, coordinating and following up on the components of the education system, including the material and human elements, in order to achieve efficiency and effectiveness of this human industry, which represents the outputs of the skilled workforce from top to bottom, as the skills of the workforce tend to become the main competitive weapon. In the twenty-first century.